2012
DOI: 10.2334/josnusd.54.177
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of tooth mobility with systemic bone mineral density and periodontal status in Indian women

Abstract: Imbalanced bone remodelling associated with osteopaenic or osteoporotic conditions can lead to a net bone loss throughout the skeleton, including the oral cavity, possibly leading to tooth mobility. This study investigated possible associations between systemic bone mineral density and both tooth mobility and periodontal status in peri-menopausal women. Subjects comprised 119 dentate, perimenopausal Indian women between 40 and 54 years old. Clinical parameters recorded were systemic bone mineral density (BMD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
4
0
5
Order By: Relevance
“…Most of the participants in the osteoporotic group were aged 50–60 years, whereas in the non‐osteoporotic group, most of the participants were aged 45–50 years. This is in line with most studies where the age range of postmenopausal women participants was found to be between 45 and 78 years …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of the participants in the osteoporotic group were aged 50–60 years, whereas in the non‐osteoporotic group, most of the participants were aged 45–50 years. This is in line with most studies where the age range of postmenopausal women participants was found to be between 45 and 78 years …”
Section: Discussionsupporting
confidence: 93%
“…This is in line with most studies where the age range of postmenopausal women participants was found to be between 45 and 78 years. 4,5,7,[16][17][18][19][20][21][22][23][24][25] At menopause, 2-3% loss of cortical bone and 4-8% loss of trabecular bone occurs per year, respectively. The first 5-10 years after menopause are associated with a period of estrogen depletion and consequent rapid bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos estudos analisados encontraram uma relação estatisticamente significante entre a doença periodontal e a osteoporose (5,6,8,(18)(19)(20)(21)(22)(23)(24)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) mas outros não encontraram nenhuma relação entre estas doenças. (7,9,25,38) Entretanto, a interpretação dos resultados publicados é difícil, pois os estudos possuem diferentes metodologias o que limita a comparação entre eles e o conhecimento atual não é suficiente para uma conclusão definitiva.…”
Section: Discussionunclassified
“…Vishwanath et al (33) Um recente estudo realizado por Bertulucci et al (34) com 99 mulheres na pós-menopausa mos-trou que o grupo com osteoporose apresentou maior NIC, PS, IG e IP. Singh et al (35) em um estudo com 119 mulheres concluiram que há uma correlação significativa entre a DMO e a mobilidade dentária, mesmo após os possíveis fatores de confundimento.No recente estudo de Gomes-Filho, (36) os resultados mostram que a osteoporose pode afetar o periodonto, visto que a recorrência da doença periodontal após o tratamento foi mais frequente em indivíduos com osteoporose.…”
Section: Revisão De Literaturaunclassified
“…, Singh et al. ). In traumatology, TM is assessed regularly when monitoring splint therapy and for diagnosing tooth ankylosis (Mackie et al.…”
mentioning
confidence: 99%